Copper-doped lanthanum manganite La0.65Ce0.05Sr0.3Mn1−xCuxO3 influence on structural, magnetic and magnetocaloric effects. Issue 13 (13th February 2018) - Chebaane, M.; Bellouz, R.; Oumezzine, Ma.; Hlil, E. K.; Fouzri, A.
Abstract : Bulk nanocrystalline samples of La0.65 Ce0.05 Sr0.3 Mn1− x Cu x O3 (0 ≤ x ≤ 0.15) manganites are prepared by the sol–gel based Pechini method. Abstract : Bulk nanocrystalline samples of La0.65 Ce0.05 Sr0.3 Mn1− x Cu x O3 (0 ≤ x ≤ 0.15) manganites are prepared by the sol–gel based Pechini method. The effect of the substitution for Mn with Cu upon the structural and magnetic properties has been investigated by means of X-ray diffraction (XRD), Raman spectroscopy and dc magnetization measurements. The structural parameters obtained using Rietveld refinement of XRD data showed perovskite structures with rhombohedral ( R 3̄ c ) symmetry without any detectable impurity phase. Raman spectra at room temperature reveal a gradual change in phonon modes with increasing copper concentration. The analysis of the crystallographic data suggested a strong correlation between structure and magnetism, for instance a relationship between a distortion of the MnO6 octahedron and the reduction in the Curie temperature, T c . A paramagnetic to ferromagnetic phase transition at T C is observed. The experimental results confirm that Mn-site substitution with Cu destroys the Mn 3+ –O 2− –Mn 4+ bridges and weakens the double exchange (DE) interaction between Mn 3+ and Mn 4+ ions, which shows an obvious suppression of the FM interaction in the La0.65 Ce0.05 Sr0.3 Mn1− x Cu x O3 matrix. The maximum magnetic entropy change −Δ S maxM is found to decrease with increasing Cu content from 4.43 J kg −1 K −1 for x = 0 to 3.03 J kg −1 K −1 for x = 0.15 upon a 5 T applied field change.